Boosting low-temperature de/re-hydrogenation performances of MgH2 with Pd-Ni bimetallic nanoparticles supported by mesoporous carbon. (23rd April 2019) - Cheng, Honghui; Chen, Gang; Zhang, Yao; Zhu, Yunfeng; Li, Liquan
Abstract: Bimetallic Pd-Ni nano-particles supported by a mesoporous carbon material CMK-3 (denoted as Pd30 Ni70 /CMK-3) were synthesized through solution impregnation and hydrogen reduction methods. Among those hierarchical Ni-Pd nano-particles, majorly large ones (>10 nm) are dispersed over the surface of CMK-3, while a litter small ones (<10 nm) are embedded into the pores. It significantly improves the de/re-hydrogenation performances of MgH2 at low temperature. The onset desorption temperature of MgH2 -Pd30 Ni70 /CMK-3 is lowered by 150 K from that of pristine MgH2 (above 593 K). About 6 wt% hydrogen could be released during its decomposition below 561 K. Noticeably, MgH2 -Pd30 Ni70 /CMK-3 is capable of releasing 1.3 wt% H2 even at 373 K. 4 wt% hydrogen can be absorbed at 343 K under a hydrogen pressure of 3 MPa within 18000 s. Activation energy values of both hydrogen decomposition (65.9 kJ mol −1 ) and absorption (78.9 kJ mol −1 ) for MgH2 -Pd30 Ni70 /CMK-3 are greatly improved from those of as-milled MgH2 . Thermal stability of the composite system is remarkably destabilized by 4.3 kJ mol H2 −1 from pristine MgH2 according to pressure-composition isotherm curves and van't Hoff plots. The enhanced performances can be ascribed to the synergistic effects of both destabilization and catalysis from nano-dispersed Pd and Ni particles, respectively. Highlights: The synergistic effect of bi-metallic nano-dispersed Pd and Ni in MgH2 system. The de/re-hydrogenation temperature was significantly reduced. Activation energy and enthalpy calculations of Mg and MgH2 system. Pd serves as reagent while Ni plays a role of catalyst in MgH2 system.